2015
DOI: 10.1242/bio.012351
|View full text |Cite
|
Sign up to set email alerts
|

Neurl4 contributes to germ cell formation and integrity inDrosophila

Abstract: Primordial germ cells (PGCs) form at the posterior pole of the Drosophila embryo, and then migrate to their final destination in the gonad where they will produce eggs or sperm. Studies of the different stages in this process, including assembly of germ plasm in the oocyte during oogenesis, specification of a subset of syncytial embryonic nuclei as PGCs, and migration, have been informed by genetic analyses. Mutants have defined steps in the process, and the identities of the affected genes have suggested bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…This suggests that germ cell specification might be particularly sensitive to the activities of centrosome-associated proteins. Consistent with this, a role for Neurl4, a centrosome-associated protein, in germ cell specification and integrity has recently been revealed ( Jones and Macdonald, 2015 ).…”
Section: Introductionsupporting
confidence: 57%
“…This suggests that germ cell specification might be particularly sensitive to the activities of centrosome-associated proteins. Consistent with this, a role for Neurl4, a centrosome-associated protein, in germ cell specification and integrity has recently been revealed ( Jones and Macdonald, 2015 ).…”
Section: Introductionsupporting
confidence: 57%
“…The three strongest interacting partners were SEC23IP, SRGAP2 and NEURL4 (Supplementary Fig. 5a ), which are linked to development 51 , 55 , 56 . These proteins are already reported to interact with HERC2 in human cell lines, validating our data 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that Neurl4 is required for initial steps of germplasm assembly during gametogenesis in Drosophila 15 . Neurl4 mutant embryos in Drosophila had reduced number of primordial germ cells as well as occurrence of primordial germ cells with abnormal morphology.…”
Section: Discussionmentioning
confidence: 97%